A Study on Factors Influencing the Inheritance Dilemma of Traditional Minority Sports Culture - Jiang, Caixia (Quality in Sport, 2025)
The inheritance dilemma of traditional minority sports culture in the New Era of Chinese Socialism was investigated using a field survey and literature review, and its influencing factors were explored. The results demonstrated that the inheritance of traditional minority sports culture is affected by various factors, such as a diversified ecological environment, socioecological trend, and a lack of cultural consciousness: (1) economization of natural ecological environment and homogenization of cultural inheritance space in the minority regions; (2) diversification of cultural, ecological environment, marginalization of traditional minority sports culture; (3) absence of successors to traditional culture; (4) imbalance in cultural inheritance methods. The traditional minority sports culture faces a severe identity crisis and a lack of cultural consciousness.